Rapid bedside testing for septic arthritis: evaluating cost-effective diagnostic tools - Pranav Rajasekharan; Atmananda Hegde; Prajwal Mane; Chethan Shetty; Rishit Anand (Journal of Infection in Developing Countries)
Introduction: Diagnosing septic arthritis through synovial fluid culture and analysis can be time-consuming, and the limited accessibility of these tests in primary and secondary healthcare centers restricts their utility in emergency situations. Therefore, there is a pressing need for an alternative, rapid, and reliable test to significantly reduce morbidity. This study aimed to evaluate the efficacy of leucocyte esterase (LE) and glucose reagent strip tests for the early diagnosis of septic arthritis.